Fast modelling of field evaporation in atom probe tomography using level set methods - Fletcher, C; Moody, M; Haley, D (IOP Publishing, 2019)
Current imaging algorithms in atom probe tomography (APT) assume a simple geometric model for the trajectories of evaporated ions between the emitter and detector. Such point-projection approaches fail to incorporate changes in sample geometry due to different phase evaporation behaviour, leading to severe distortions in reconstructed APT data. Here we propose a new approach to APT reconstruction where a continuum model is used to account for changes in sample geometry. A 2D model is demonstrated, readily extendable to 3D, capable of simulating the complete evaporation of samples within minutes, while accounting for dielectric and crystallographic behaviour. Ion trajectories are calculated from the sample surface onto a simulated detector, allowing for the accurate mapping of detector positions onto the sample surface throughout time. Such an approach could drive a new reconstruction algorithm applicable to full size experimental datasets that can correct for the distortions currently present within APT reconstructions.